DETERMINAN YANG MEMPENGARUHI KEJADIAN DIABETES MELITUS TIPE 2 - Blaire Wismar Panjaitan, Norman; Martiar Siahaan, Jekson; Sinurat, Suryati (Jurnal Kedokteran Methodist, 2022)
Background: Diabetes mellitus (DM) is included in the list of health problem the highest number of patients today.The world community who have DM disease is around 422 million in 2014. The most affected countries are underdeveloped countries, including Indonesia. Based on research by the International Diabetes Federation (IDF), there will be an increase in DM from year to year. So there will be many who suffer from DM. DMT2 is a long-term metabolic disorder characterized by increased blood glucose levels (BGL) caused by damage to pancreatic beta cells and can occur because patients are obese. The clinical symptoms of DM are excessive appetite, excessive thirst and an inappropriate urge to urinate and sudden weight loss. Of the many types of DM, the one with the most sufferers is Diabetes Mellitus Type 2 (T2DM). T2DM occurs due to multiple etiologies. Age factor can also cause T2DM because insulin production has decreased so that BGL can increase and cause T2DM. Method : The research method used is Literature research, using secondary data. The data are combined using documentation techniques. The medical journals used were 5 journals in accordance with the Indonesian language inclusion criteria, with the research subjects of T2DM patients, and full text publications. Result : There is a assosiation between BGL, BMI, HbA1C, and genetics on the incidence of T2DM . Conclusion: There is an assosiation between BGL, blood pressure, BMI, HbA1C, and genetics on the incidence of T2DM.